Secondary growth synthesis of covalent organic framework modified electrospun nanofibers for extraction of estrogens in milk samples - Yang, Dayu; Li, Si; Zhao, Deyi; Zou, Ting; Liu, Xiaoyan; Pang, Jie; Zhuang, Weijing; Yan, Zhiming (Journal of food composition and analysis, 2023)
In this work, novel covalent organic framework modified polyacrylonitrile electrospun nanofibers (denoted: PAN@COF(TFP-p-PDA) nanofibers) was prepared and used as adsorbent of pipette tip solid-phase extraction (PT-SPE) for the effective extraction of estrogens in milk followed by high-performance liquid chromatography-fluorescence detector (HPLC-FLD). The PAN@COF(TFP-p-PDA) nanofibers was prepared via a secondary growth method for the first time. The characterization results of PAN@COF(TFP-p-PDA) nanofibers showed that a continuous, dense and uniform COFs layer was grown on the surface of PAN electrospun nanofibers, and PAN@COF(TFP-p-PDA) nanofibers had high Brunauer-Emmett-Teller (BET) specific surface area (303.91 m2 g−1). Several important parameters of PT-SPE affecting the extraction efficiency were systematically studied, and the optimized conditions were comprised of 8 mg PAN@COF(TFP-p-PDA) nanofibers, pH 7 and 1.5 mL of 15% ammonia-acetonitrile (V:V) as elution solvent. Under optimal conditions, the linear range of the tested estrogen was estimated from 1.13 to 100 ng mL−1 with correlation coefficient larger than 0.997. The limits of detection (LOD) and limit of quantification (LOQ) were calculated as 0.34–0.57 ng mL−1 and 1.13–1.9 ng mL−1, respectively. The practicality of the developed analytical method was verified through determination of estrogens in milk samples, satisfactory recoveries (87.0%−114.8%) were obtained with relative standard deviations (RSDs) smaller than 8.6%.